# 5x^2=29x+6

## Simple and best practice solution for 5x^2=29x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 5x^2=29x+6 equation:

Simplifying
5x2 = 29x + 6

Reorder the terms:
5x2 = 6 + 29x

Solving
5x2 = 6 + 29x

Solving for variable 'x'.

Reorder the terms:
-6 + -29x + 5x2 = 6 + 29x + -6 + -29x

Reorder the terms:
-6 + -29x + 5x2 = 6 + -6 + 29x + -29x

Combine like terms: 6 + -6 = 0
-6 + -29x + 5x2 = 0 + 29x + -29x
-6 + -29x + 5x2 = 29x + -29x

Combine like terms: 29x + -29x = 0
-6 + -29x + 5x2 = 0

Factor a trinomial.
(-1 + -5x)(6 + -1x) = 0

Subproblem 1Set the factor '(-1 + -5x)' equal to zero and attempt to solve:

Simplifying
-1 + -5x = 0

Solving
-1 + -5x = 0

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -5x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -5x = 0 + 1
-5x = 0 + 1

Combine like terms: 0 + 1 = 1
-5x = 1

Divide each side by '-5'.
x = -0.2

Simplifying
x = -0.2
Subproblem 2Set the factor '(6 + -1x)' equal to zero and attempt to solve:

Simplifying
6 + -1x = 0

Solving
6 + -1x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = 0 + -6
-1x = 0 + -6

Combine like terms: 0 + -6 = -6
-1x = -6

Divide each side by '-1'.
x = 6

Simplifying
x = 6Solutionx = {-0.2, 6}`